Angiotensin 1 peptide-conjugated CdSe/ZnS quantum dots for cardiac-specific hydrogen sulfide targeted therapy in myocardial ischemia-reperfusion injury - Wang, Qing; Xue, Xiaofei; Wang, Pei; Yu, Yue; Wang, Jun; Jiang, Qixia; Xiao, Jian (Frontiers in Pharmacology, 2024)
In this investigation, we explored a novel strategy to mitigate myocardial ischemia/reperfusion (I/R) injury through targeted delivery of hydrogen sulfide (H2S) using angiotensin 1 (AT1) peptide-conjugated CdSe/ZnS quantum dots. These nanocarriers transport the cystathionine-γ-lyase (CSE) plasmid specifically to the myocardium, enhancing H2S production locally. Traditional methods, like venous NaHS injection or adenovirus-mediated CSE gene delivery, are limited by low efficiency and adverse effects. Our approach ensures the nanocarrier predominantly accumulates in the heart, as confirmed by in vivo fluorescence imaging, without affecting other organs. Analysis showed significantly higher CSE expression in the heart of the AT1-nanocarrier group than in controls. The therapeutic efficacy was evidenced by reduced myocardial infarct size, improved cardiac function, decreased cell death, and lower oxidative stress in vitro. Importantly, we observed a reduction in key markers of endoplasmic reticulum stress and mitophagy, indicating that the protective effects are mediated through the CHOP/GRP78/eIF2a signaling pathway.The adenovirus vector carrying the CHOP gene reversed the reduced mitophagy, underscoring the pathway's role. Our findings offer a promising avenue for precise, side-effect-free cardiac therapy, highlighting the potential of targeted nanocarriers in treating myocardial ischemia/reperfusion injury.